Development of Blog-Based Audio Visual Learning Media to Improve Student Learning Interests in Money and Banking Topic - Lilis Mutia; Gimin Gimin; Mahdum Mahdum (Universitas Riau, 2020)
This research aims to produce audio-based learning media for blogs on the subjects of money and banking. This study used research and development methods with 4D Thiagarajan. There are four stages in Thiagarajan's 4D model; the initial needs analysis stage (define), the prototype (design) stage, the development stage based on expert advice and the field trial (develope), and the publication stage (disseminate). The data analysis technique used was quantitative descriptive technique. The results of research and development carried out in the form of audio-based learning media blog on economic subjects of money & banking material which contains a homepage, learning tools, learning materials, videos, LKPD, assignments, commentary features and social media. The audio-visual media based on money & banking material developed was very good ratings from media experts with an average score of 4 (after revision) and a material expert of 3.6 (scale 4). Students also gave a good response with an overall average score of 3.6, and an increase in student interest in learning with a difference of greater than 1 is 28.63%.